Synthesis of natural deep eutectic solvents using a mixture design for extraction of animal and plant samples prior to ICP-MS analysis - Santana, Ana P.R. [UNESP]; Andrade, Daniel F.; Guimarães, Taciana G.S. [UNESP]; Amaral, Clarice D.B.; Oliveira, Andrea; Gonzalez, Mario H. [UNESP] (Elsevier, 2020)
Solvents with both low density and viscosity have the advantage of higher extraction efficiency due to lower diffusivity and consequently higher mass transfer. In this study, a mixture design was performed for the synthesis of three different natural deep eutectic solvents (NADES) using citric acid, malic acid, and xylitol. The optimized proportion for each of the three solvents synthesized was selected based on density and viscosity values. The NADES were characterized by infrared spectroscopy analysis, that showed characteristic bands of the initial reagents and the presence of hydrogen bonds confirming the formation of each deep eutectic solvent. Then, the NADES were used as solvents in ultrasound-assisted extraction (UAE) and microwave-assisted extraction (MAE) of biological tissue and plant material samples for the determination of As, Cd, Hg, Pb, Se, and V by inductively coupled plasma mass spectrometry (ICP-MS). The results for the proposed methods were compared to microwave-assisted acid digestion (MW-AD). The extraction recoveries ranged from 80 to 120% for most of the elements determined. The use of NADES as carbon sources improved the sensitivity of the As and Cd analyses, due to charge transfer reactions between the analyte and C+ and/or other carbon species. In addition, the Analytical Eco-Scale was used to assess the greenness of the proposed analytical procedures (UAE and MAE). It showed that the UAE and MAE methods provided excellent green analyses, while the MW-AD method was rated as an acceptable green procedure.
Keywords: Green analytical chemistry; ICP-MS; MAE; Sample preparation; UAE